Common fixed points for family of mappings - D. E. Anderson; K. L. Singh; J. H. M. Whitfield (International Journal of Mathematics and Mathematical Sciences)
The main aim of the present paper is to prove the existence of common fixed points for mappings which are not necessarily continuous. Our results, which are primarly motivated by investigation of Husain and Sehgal (Bull. Austral. Math. Soc. 13 (1975), 261-267), generalize the results of Husain and Sehgal, Sehgal, Kannan, Reich, Hardy and Rogers, and others.